2022
DOI: 10.1101/2022.04.25.22274035
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Critical interventions for demand generation in Zambia, Nepal, and Senegal with regards to the 5C psychological antecedents of vaccination

Abstract: IntroductionChildhood vaccination is an effective intervention for lowering the burden of infectious disease. Progress was made to increase coverage globally, but vaccine hesitancy and refusal has threatened to erode said increases. The 5C psychological antecedents of vaccination (“5C”) model provides a validated measure of “vaccine hesitancy or confidence” to assess individual thoughts and behaviors behind vaccination. Our purpose was to investigate population-level factors that contributed to high and sustai… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…As frontline health workers, CHWs play a critical role in routine vaccination programming by generating demand for childhood vaccination; connecting community members to the formalized health care system; and working closely with and in communities, schools, and religious facilities [9,10]. A concurrent analysis of our research showed that CHWs played a crucial role in demand generation in Nepal, Senegal, and Zambia [11][12][13][14]. The WHO health policy guidelines for CHWs program (2018) recommends the following: 1) community engagement in selection, 2) training, 3) remuneration, and 4) supervision.…”
Section: Introductionmentioning
confidence: 73%
“…As frontline health workers, CHWs play a critical role in routine vaccination programming by generating demand for childhood vaccination; connecting community members to the formalized health care system; and working closely with and in communities, schools, and religious facilities [9,10]. A concurrent analysis of our research showed that CHWs played a crucial role in demand generation in Nepal, Senegal, and Zambia [11][12][13][14]. The WHO health policy guidelines for CHWs program (2018) recommends the following: 1) community engagement in selection, 2) training, 3) remuneration, and 4) supervision.…”
Section: Introductionmentioning
confidence: 73%
“…As front-line health workers, CHWs play a critical role in routine vaccination programming by generating demand for childhood vaccination; connecting community members to the formalised healthcare system; and working closely with and in communities, schools and religious facilities 10 11. A concurrent analysis of our research showed that CHWs played a crucial role in demand generation in Nepal, Senegal and Zambia 12 13. The WHO health policy guidelines for CHWs programme (2018) recommend the following: (1) community engagement in selection, (2) training, (3) remuneration and (4) supervision.…”
Section: Introductionmentioning
confidence: 73%
“…Further analysis of community health worker programmes and demand generation activities in Nepal, Senegal, and Zambia will be detailed in our upcoming publications. 31 …”
Section: Resultsmentioning
confidence: 99%
“…(National-level government stakeholder, Senegal) Further analysis of community health worker programmes and demand generation activities in Nepal, Senegal, and Zambia will be detailed in our upcoming publications. 31 Adaptation at all levels of the health system In Nepal, Senegal and Zambia, decision-makers and implementers at the national, subnational, and community levels demonstrated their ability to consider contextual factors, evaluate or reflect on quality data and tailor vaccine programming based on local needs and priorities.…”
Section: Government-led Community Engagement Initiativesmentioning
confidence: 99%